A retrospective study of insurance coverage status and economic cost of rare diseases in Hainan Province - John Sieh Dumbuya; Xiuling Chen; Lin Deng; Bashir Ahmad; Jun Lu (Scientific Reports)
Abstract Rare diseases present a significant economic burden on patients, families, and healthcare systems worldwide. As the prevalence of these diseases rises in China, data regarding their impact, specifically in Hainan Province, is scarce. Thus, this study aims to evaluate insurance coverage, economic costs, and the factors contributing to the burden of rare diseases in Hainan. We employed a bottom-up approach to analyse the prevalence and economic burden from 2019 to 2023, utilising data from the Hainan Provincial Health Commission Databases. We assessed insurance coverage as well as expenditures related to hospitalisation, diagnostics, medications, surgery, and out-of-pocket costs. Of 4,975 patients diagnosed with 99 distinct rare diseases, 83.01% were insured. From 2019 to 2023, the number of patients increased from 760 to 1,328, while economic costs surged from 34.26 million CNY (US$ 4.89 million) to 64.74 million CNY (US$ 8.86 million). Thalassemia major, one of the most prevalent conditions, generated the highest costs. Hospitalisation expenses accounted for 49.16% of the total costs, with out-of-pocket expenses averaging 17.52%. The findings reveal a significant economic burden associated with rare diseases in Hainan, highlighting the necessity for targeted policy interventions. Furthermore, additional research is needed to refine estimates of this economic burden.